A clinical epidemiological study of gallbladder carcinoma: a retrospective study - Sahai, Shweta (International Journal of Advances in Medicine, 2019)
Background: Incidence of gallbladder carcinoma (GBC) is high among the north Indian population. It may be due to environmental, dietary and reproductive factors. Evaluation of GBC epidemiology will provide important insights into determining causes and risk factors for gallbladder cancer. The aims and objectives were to study the epidemiology, clinical presentation and etiological factors of GBC. Methods: Fifty-one cases of GBC were studied retrospectively at Cancer Hospital and Research Institute (CHRI) Gwalior, Madhya Pradesh, India from January to December 1998. All the patients underwent a detailed history taking and physical examination followed by routine laboratory tests and other investigations including ultrasonographic and computed tomography scan of whole abdomen. Histopathological evaluation of gallbladder specimen was also performed after surgical resection of the GB mass. Results: Incidence of GBC at this centre was 1.49%. GBC was more prevalent among old women (mean age 52.62±12.14 years) belonging to low socio-economic status (SES) (52.94%). Most common presenting symptom of GBC was pain in right hypochondrium (70.4%) followed by anorexia (42.8%), pruritus (35.7%), weight loss (31.2), nausea and vomiting (30.4%). Histopathological examination revealed majority of the case to have adenocarcinoma (84.31%). Gallstones were present in 35.29% patients. Conclusions: GBC is more prevalent in older women belonging to low SES. Gallstones remain the chief risk factor for this malignancy. Histopathological examination of all cholecystectomy specimens for early pre cursor lesion could serve as an important means of early detection of this carcinoma.